Nicotinic acetylcholine receptors in a songbird brain. Issue 11 (28th March 2022) - Asogwa, Norman Chinweike; Toji, Noriyuki; He, Ziwei; Shao, Chengru; Shibata, Yukino; Tatsumoto, Shoji; Ishikawa, Hiroe; Go, Yasuhiro; Wada, Kazuhiro
Abstract: Nicotinic acetylcholine receptors (nAChRs) are ligand‐gated ion channels that mediate fast synaptic transmission and cell signaling, which contribute to learning, memory, and the execution of motor skills. Birdsong is a complex learned motor skill in songbirds. Although the existence of 15 nAChR subunits has been predicted in the avian genome, their expression patterns and potential contributions to song learning and production have not been comprehensively investigated. Here, we cloned all the 15 nAChR subunits (ChrnA1–10, B2–4, D, and G) from the zebra finch brain and investigated the mRNA expression patterns in the neural pathways responsible for the learning and production of birdsong during a critical period of song learning. Although there were no detectable hybridization signals for ChrnA1, A6, A9, and A10, the other 11 nAChR subunits were uniquely expressed in one or more major subdivisions in the song nuclei of the songbird brain. Of these 11 subunits, ChrnA3–5, A7, and B2 were differentially regulated in the song nuclei compared with the surrounding anatomically related regions. ChrnA5 was upregulated during the critical period of song learning in the lateral magnocellular nucleus of the anterior nidopallium. Furthermore, single‐cell RNA sequencing revealed ChrnA7 and B2 to be the major subunits expressed in neurons of the vocal motor nuclei HVC and robust nucleus of the arcopallium, indicating the potential existence of ChrnA7‐homomeric and ChrnB2‐heteromeric nAChRs in limited cell populations. These results suggest that relatively limited types of nAChR subunits provide functional contributions to song learning and production in songbirds. Abstract : The expression of nicotinic acetylcholine receptors (ChrnA1–10, B2–4, D, and G) in the zebra finch brain showing unique differential expressions in subdivisions of the forebrain and the song nuclei. The white color represents mRNA signal.